Impact Of Integrated Performance Indicators On Clinical Outcomes And Patient Satisfaction In Hospitals: A Systematic Review And Global Analysis (The Review of Diabetic Studies, 2024)
Background: Healthcare institutions worldwide seek to improve service quality and operational efficiency, with performance indicators emerging as essential tools for evaluating, managing, and enhancing hospital care.Objective:This systematic review aims to analyze the impact of hospital performance indicators on patient clinical outcomes and satisfaction levels, and to identify relationships between different types of indicators and achieved results.Methods:The review followed the PRISMA framework, including a comprehensive search in PubMed, Scopus, Web of Science, and Google Scholar databases for studies published between 2015-2024. A total of 47 studies meeting inclusion criteria were analyzed, with performance indicators classified according to the Donabedian model.Results: The review revealed a strong positive relationship between performance indicator implementation and improved clinical outcomes, with reductions in infection rates (28%), mortality rates (17%), length of stay (15%), readmission rates (19%), and improvement in patient satisfaction (32%). Hospitals adopting a balanced approach incorporating indicators from all categories achieved better results than those focusing on a single category.Conclusions: Performance indicators, when applied in an integrated and thoughtful manner, provide an effective tool for improving hospital processes and patient experiences. The study recommends adopting a multi-dimensional approach to performance measurement, involving patients in defining quality criteria, and utilizing digital platforms for real-time monitoring.